2009
DOI: 10.1039/b907878a
|View full text |Cite
|
Sign up to set email alerts
|

Caffeoyl and cinnamoyl clusters with anti-inflammatory and anti-cancer effects. Synthesis and structure–activity relationship

Abstract: The syntheses of twelve caffeoyl/cinnamoyl clusters and their anti-inflammatory and anti-cancer effects are described. Synthesis of the title compounds involved a multiple copper(I)-catalyzed Huisgen 1,3-dipolar cycloaddition. Azide or alkyne functionalized cinnamoyl or caffeoyl moieties are attached to the selected core molecules to allow variation of the introduced cinnamoyl or caffeoyl moieties in order to compare their effects on 5-lipoxygenase (5-LO) inhibition and on cell proliferation in cancerous (MCF7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 56 publications
3
29
0
Order By: Relevance
“…Hydroxy-bearing cinnamic acids are naturally abundant antioxidants in our diet, such as pcoumaric acid, and caffeic acid, which have a variety of biological activities, such as anticancer [3], antimutation [4], and antioxidation [5], hepatoprotective etc [6,7]. Some hydroxybearing cinnamaldehydes, such as ocoumaraldehyde from bark of cinnamon,p-coumaraldehyde, ferulaldehyde,and caffeic aldehyde have been widely studied and found to be good bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxy-bearing cinnamic acids are naturally abundant antioxidants in our diet, such as pcoumaric acid, and caffeic acid, which have a variety of biological activities, such as anticancer [3], antimutation [4], and antioxidation [5], hepatoprotective etc [6,7]. Some hydroxybearing cinnamaldehydes, such as ocoumaraldehyde from bark of cinnamon,p-coumaraldehyde, ferulaldehyde,and caffeic aldehyde have been widely studied and found to be good bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, assays of multivalent compounds showed that inhibitory activity of caffeates is not proportional to the number of caffeoyl groups present in a compound . Although most of the caffeoyl esters synthesized in these studies had excellent and similar 5‐LO inhibition potential in HEK293 cell lysates, large variability in inhibition was found when performing assays on whole cells . Such differences in activity among structurally similar compounds possessing identical pharmacophores may indicate the important influence of structure and steric bulk on cell permeability and hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 86%
“…However, antioxidant activity is not sufficient to assure efficient 5‐LO inhibition in complex systems: caffeic acid ( 2 ) and the amide analog of CAPE ( 3 ), which are roughly equipotent with CAPE ( 3 ) in radical scavenging assays, possess far lower inhibitory activity in PMNL and whole blood assays than CAPE ( 3 ) . Furthermore, assays of multivalent compounds showed that inhibitory activity of caffeates is not proportional to the number of caffeoyl groups present in a compound . Although most of the caffeoyl esters synthesized in these studies had excellent and similar 5‐LO inhibition potential in HEK293 cell lysates, large variability in inhibition was found when performing assays on whole cells .…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations